2018
DOI: 10.1002/syn.22024
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Taiep rats have shorter dendritic trees in the dorsal field of the hippocampus without spatial learning disabilities

Abstract: Myelin mutant taiep rats show a progressive demyelination in the central nervous system due to an abnormal accumulation of microtubules in the cytoplasm and the processes on their oligodendrocytes. Demyelination is associated with electrophysiological alterations and the mutant had a progressive astrocytosis. The illness is associated with change in cytokine levels and in the expression of different nitric oxide synthase and concomitantly lipoperoxidation in several areas of the brain. However, until now there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(35 reference statements)
1
1
0
Order By: Relevance
“…This particular difference could indicate degradation of neurons near this area. Other studies confirm the presence of morphological (Silva-Gómez et al, 2018) and physiological (Fuenzalida et al, 2009) changes in the taiep hippocampus.…”
Section: Discussionsupporting
confidence: 54%
“…This particular difference could indicate degradation of neurons near this area. Other studies confirm the presence of morphological (Silva-Gómez et al, 2018) and physiological (Fuenzalida et al, 2009) changes in the taiep hippocampus.…”
Section: Discussionsupporting
confidence: 54%
“…Recent studies have demonstrated the importance of the CD95/CD95L pathway to the nervous system, which is involved in the occurrence and development of a variety of neurological diseases such as AD, [38][39][40][41] but whether it is associated with neuropathic pain is not clear. The main function of CD95/CD95L is to participate in the immune response, etc.…”
Section: Discussionmentioning
confidence: 99%